3D printing of lubricative stiff supramolecular polymer hydrogels for meniscus replacement. (13th July 2021) - Fan, Chuanchuan; Xu, Ziyang; Wu, Tengling; Cui, Chunyan; Liu, Yang; Liu, Bo; Yang, Jianhai; Liu, Wenguang
Abstract : Thickening a concentrated solution of a multiple-H-bonding monomer (MHM) and a zwitterion monomer (ZM) with a soft poly(MHM- co -ZM) gel enables direct printing of the MHM, and post-polymerization generates a stiff and lubricative hydrogel meniscus. Abstract : 3D printing of a stiff and lubricative hydrogel-based meniscus substitute has been challenging since printability and stiffness compromise each other. In this work, based on an upgraded self-thickening and self-strengthening strategy, a unique multiple H-bonding monomer N -acryloylsemicarbazide (NASC) is firstly copolymerized with a super-hydrophilic monomer carboxybetaine acrylamide (CBAA) in dimethyl sulfoxide (DMSO)/H2 O to form a soft poly(NASC- co -CBAA) gel, in which PCBAA serves to weaken the H-bonding interaction and avoid hydrophobic phase separation. The poly(NASC- co -CBAA) gel is then loaded with concentrated NASC and CBAA, followed by heating to form a thickening sol ink, which is printed into different objects that are further photoirradiated to initiate the copolymerization of entrapped NASC and CBAA, resulting in the formation of a high performance hydrogel with a Young's modulus of 10.98 MPa, tensile strength of 1.87 MPa and tearing energy of 5333 J m −2 after DMSO is completely replaced with water, due to the re-establishment of NASC H-bonds. Importantly, PCBAA affords high lubricity in printed hydrogels. The printed PNASC–PCBAA meniscus substitute can substitute rabbit's native meniscus and ameliorate the cartilage surface wear within a set 12-week time window, portending great potential as a meniscal substitute and other soft-supporting tissue scaffolds.